Present Land Use and Land Use Zoning of Kushma Municipality: A Comparative Assessment with Cadastral Superimpose - Subedi, Sushmita; Pandit, Roman; G.C., Manoj; Subedi, Indra (Journal on Geoinformatics, Nepal, 2025)
Rapid urbanization and unplanned expansion in Nepal have necessitated a structured land use planning to balance economic growth, environmental sustainability and disaster resilience. This study conducts a comparative assessment of present land use and land use zoning in Kushma Municipality integrating cadastral data to evaluate alignment with the national land use policy. Using Geographic Information System (GIS), high-resolution satellite image and multi-criteria analysis, the research maps current land use patterns and land use zoning framework in the municipality. Results reveal agricultural dominance in present land use with 60.81% of total area followed by forest cover. Land use zoning indicates a 13.23% reduction in agricultural land, offset by substantial expansions in residential area by 10.65%. Cadastral superimposition highlights discrepancies, with agricultural parcels decreasing from 51.90% to 41.78%, while commercial areas triple in allocated space. The study underscores the need for adaptive land use policies, periodic zoning revisions and community engagement to ensure sustainable development. By integrating GIS-driven insights with participatory planning, Kushma Municipality can navigate urbanization challenges while safeguarding ecological and agricultural assets. This research contributes a replicable framework for municipalities in developing regions aiming to harmonize cadastral data, land use planning and policy implementation.